Recent Advances on Nanotechnology Applications to Cancer Drug Therapy - Bellera, Carolina Leticia (2013)
One of the greatest challenges in cancer drug therapy is to maximize the effectiveness of the active ingredient while reducing its systemic adverse effects. Conventional (non-targeted) systemic drug therapy is characterized by unspecific distribution of the anticancer drugs: both healthy and affected tissues are thus exposed to the chemotherapeutic agent, giving raise to off-target side-effects. Besides, a number of widely-used chemoterapeutic agents present unfavorable physicochemical properties, such as low solubility or low stability issues, limiting their available routes of administration and therapeutic applications. Nano-delivery systems seem as promising solutions to these issues. They can be used for targeted-drug release, diagnostic imaging and therapy monitoring. Nanosystems allow the formulation of drug delivery systems with tailored properties (e.g. solubility, biodegradability, release kinetics and distribution) that provide means to improve cancer patients? quality of life by lowering the administered dose and, incidentally, the cost of clinical treatments. This article overviews the main features of different nanovehicles (linear and non-linear polymeric nanosystems, lipid-based systems, inorganic nanoparticles) and presents a selection of reports on applications of such systems to cancer therapy published between 2011 and 2013.